DISTRIBUTION, DENSITY, AND BIOLOGICAL ASPECT OF Trichiurus lepturus IN THE SOUTHERN OF JAVA. INDIAN OCEAN EEZ OF INDONESIA - Fayakun Satria; Wudianto Wudianto; Awwaludin Awwaludin (Research Center for Fisheries, 2007)
Distribution, density, and biological aspect ol Trichiurus lepturus in deeper parts of southern Jawa are described based on data obtained from research cruise in May 2005. The cruise has successfully made 52 stations of trawl across southern of Java.